Revisiting the semi-convocational model: democratic failure in prewar Lebanon and post-invasion Iraq - Aboultaif, Eduardo Wassim (International Political Science Review)
This article revisits the concept of semi-consociational democracy and distinguishes it from full consociationalism. Semi-consociationalism features just two of the characteristics of full consociationalism, proportionality and segmental autonomy, and exists without strong grand coalitions and veto powers. The case studies of prewar Lebanon and post-invasion Iraq demonstrate this new category of power sharing, which relies on three conditions: concentration of executive powers in the presidential office (prewar Lebanon) or premiership (post-invasion Iraq), communal hegemony in the system, and communal control over the armed forces. Full consociationalism then is mistakenly blamed for democratic failure in these two case studies.- Reproduced
Keywords: Prewar lebanon, Post-Invasion Irag, Consociationalis, Semi-Consociationalis, Armed forces, Executive, Hegemony